The Opt-Out Movement and the Reform Agenda in U.S. Schools. Issue 5 (May 2021) - Pizmony-Levy, Oren; Lingard, Bob; Hursh, David
In this editorial, the authors situate the opt-out movement in the broader context of resistance to the global educational reform movement and its specific playing out in the USA in relation to the opt-out movement. The editors review the 11 articles and commentary and discuss the contributions of the collection as a whole to the literature. They note the contribution of the special issue to the literature on the application of social movement theory to educational politics and the literature on resistance to the global education reform movement.